Reimagining the Library as a Technology: An Analysis of Ranganathan’s Five Laws of Library Science within the Social Construction of Technology Framework - Carr, Patrick L. (My University, 2014)
S. R. Ranganathan’s five laws of library science have long been a theoretical cornerstone of librarianship. This article draws on theories in the field of technology studies to advance the claim that the enduring relevance of the five laws is rooted in how they embrace the social construction of technology (SCOT) framework, which is based in the supposition that the actions of user communities shape a technology’s meaning. After briefly discussing the five laws along with the central principles of the SCOT framework, the article analyzes how the laws map within the framework and also how the laws confound the claims of a competing theory of technology, technological determinism. The article advocates that librarians use the laws’ SCOT-based principles as a guide to navigate through a period of transformative change.
© 2014 by The University of Chicago. All rights reserved. Published version: https://www.journals.uchicago.edu/doi/10.1086/675355
Keywords: Library science; Social Construction of Technology framework; Technology; Library and information science; Social constructionism